Problems in Stem Cell Therapy for Cardiac Repair and Tissue Engineering Approaches Based on Graphene and Its Derivatives - Aslan, Ayca; Allahverdiyev, Adil M.; Bagirova, Melahat; Abamor, Emrah S. (Current Stem Cell Research & Therapy, 2018)
Background: Today, coronary artery disease is still one of the most important causes of mortality despite advanced surgical methods, pharmacotherapies and organ transplantation. These treatment modalities are intended to prevent further progression of myocardial infarction and do not involve the repair of the damaged part. Therefore, stem cell therapy has emerged as a new approach for the treatment of coronary artery disease. However, there are some restrictions that limit the use of these cells for desired repair. The leading limitation is that newly formed cardiomyocytes do not provide electrical integrity with local cells. Objective: In this paper, we review the difficulties that limit the use of stem cell therapy in cardiac repair and emphasize the importance of the integration of stem cell with tissue scaffolds with conductivity. Furthermore, significance of using graphene scaffolds in cardiac tissue engineering is highlighted due to its conductivity features. Result: Recently, the fabrication of tissue scaffoldings has made it possible to create a biomimetic cellular environment while providing a new approach to solving these problems in treatment. Especially, the integration of stem cell therapy with graphene-based tissue scaffolds with electrical conductivity, is one of the promising new strategies to turn the success of two approaches of tissue engineering into synergistic effect in cardiac repair. Conclusion: Literature analysis has demonstrated that there are some limitations in use of stem cell therapy for successful treatment of cardiac repair and graphene-based tissue engineering approaches which are promising to solve these problems in the near future.
Keywords: Conductivity